Участь населення України у волонтерській та благодійницькій діяльності - Хомяк, Андрій Олександрович; Хомяк, Андрей Александрович; Khomiak, Andrii O. (Східноєвропейський національний університет імені Лесі Українки, 2015)
На основі даних Всесвітнього індексу благодійності виявлено такі основні тенденції волонтерської та благодійницької діяльності в східноєвропейських країнах, як зниження участі населення у волонтерській діяльності й зростання пожертвування грошей, а також наявність позитивної динаміки в Україні. Згідно з даними GFK Ukraine, діяльність волонтерів в Україні орієнтована на допомогу українській армії (70 %, 2014 р.), людям похилого віку, інвалідам, дітям і т. ін. (38 %, 2014 р., 72 % до 2014 р.). Участь українців у волонтерській діяльності має ситуативний характер. Свідчення становлення інституту волонтерства в Україні – високий рівень довіри населення до волонтерів. Based on World Giving Index the main trends of voluntary and charitable activities in Eastern European countries are identified, in particular, there are the decrease of participation in volunteering activities and increase of donations of money, and the presence of positive dynamics in Ukraine (World Giving Index increase by 16 % for 6 years). According to GFK Ukraine data, we can assert that the indicator of participation in volunteering increased and the direction of the volunteers in Ukraine changed - help to the Ukrainian army (70% in 2014) is the most common form of volunteering, whilst the help to the elderly, and disabled, and children, etc. (38% in 2014, 72% for 2014) became the second. Differences between results of studies of volunteerism - GFK Ukraine and Gallup’s WorldView World Poll - confirmed that Ukrainian participation in voluntary activities has inconsistent character. However, the high level of trust in the volunteers is an evidence of the formation of the volunteering in Ukraine as a social institute.
Participation of the Population of Ukraine in Voluntary and Charitable Activities
Keywords: волонтерська діяльність; Всесвітній індекс благодійності; громадянське суспільство; благодійництво; інституціоналізація; voluntary activities; World Giving Index; civil society; charity; institutionalization